DIGIDIA-project: Experiences of video-enabled receptions for prevention of type 2 diabetes - Elisa Airikkala; Mari Laaksonen; Tuula-Maria Rintala (Finnish Social and Health Informatics Association, 2024)
The time of the COVID-19 epidemic emphasized the need for the development and implementation of remote receptions and digital services, as preventive work was reduced, and people decreased their in-person visits in health care due to fear of infections. In 2020, the diagnoses of type 2 diabetes (T2D) decreased, despite the fact that diabetes is known to be increasing. DIGIDIA (Promoting Digital Skills in the Low Labour Market-Driven Diabetes Patients) project aimed to respond to this need. The project focused on developing digital health competence, health literacy, and practices that enable preparation for future unforeseen events. The project recruited adults from Tampere who were at risk of T2D, had prediabetes, or recently received a diagnosis of type 2 diabetes (n=60). Participants were provided with a digital learning environment, workshops, and video-enabled receptions. This article presents the use of video reception and user experiences (n=52) in the project. The participants appreciated all organized activities. All but one participant felt that video-enabled reception suited them well. The majority of participants (87%) expressed a desire for using video reception again in health care settings. However, it was pointed out that this form of telemedicine might not be suitable for everyone, and concerns about data security were also raised. As a conclusion, citizens were ready to use video-enabled services in healthcare settings.  The use of video receptions should be increased in the management of type 2 diabetes (T2D).